Ganglion Cytology: A Novel Rapid Method for the Diagnosis of Equine Dysautonomia. Issue 2 (March 2019) - Piccinelli, Chiara; Jago, Rachel; Milne, Elspeth
Equine dysautonomia (grass sickness) is characterized by autonomic neuronal degeneration and is often fatal. As outbreaks occur, rapid diagnosis is essential but confirmation currently requires histological examination. This study evaluated diagnostic accuracy of cytological examination of cranial cervical ganglion (CCG) scrapings for dysautonomia diagnosis. CCG smears from 20 controls and 16 dysautonomia cases were stained with May-Grünwald Giemsa (MGG), hematoxylin and eosin (HE), and cresyl fast violet (CFV), with HE-stained histological sections of CCG as gold standard for diagnosis. Examining all 3 stains together, the sensitivity and specificity were 100%. Occasional individual smears (4/107, 3.7%) were nondiagnostic due to low cellularity, and in a few individual smears the final diagnosis was correct but more tentative (CFV: 5/33 [15.1%], HE: 2/34 [5.9%], and MGG: 4/36 [11.1%]), due to low cellularity or suboptimal cell morphology. CCG cytology was considered reliable for rapid postmortem diagnosis of equine dysautonomia, particularly using MGG.